Use of dipeptidyl peptidase‐4 inhibitors and prognosis of COVID‐19 in hospitalized patients with type 2 diabetes: A propensity score analysis from the CORONADO study. Issue 5 (16th February 2021) - Roussel, Ronan; Darmon, Patrice; Pichelin, Matthieu; Goronflot, Thomas; Abouleka, Yawa; Ait Bachir, Leila; Allix, Ingrid; Ancelle, Deborah; Barraud, Sara; Bordier, Lyse; Carlier, Aurélie; Chevalier, Nicolas; et al.
Abstract: Aim: To investigate the association between routine use of dipeptidyl peptidase‐4 (DPP‐4) inhibitors and the severity of coronavirus disease 2019 (COVID‐19) infection in patient with type 2 diabetes in a large multicentric study. Materials and Methods: This study was a secondary analysis of the CORONADO study on 2449 patients with type 2 diabetes (T2D) hospitalized for COVID‐19 in 68 French centres. The composite primary endpoint combined tracheal intubation for mechanical ventilation and death within 7 days of admission. Stabilized weights were computed for patients based on propensity score (DPP‐4 inhibitors users vs. non‐users) and were used in multivariable logistic regression models to estimate the average treatment effect in the treated as inverse probability of treatment weighting (IPTW). Results: Five hundred and ninety‐six participants were under DPP‐4 inhibitors before admission to hospital (24.3%). The primary outcome occurred at similar rates in users and non‐users of DPP‐4 inhibitors (27.7% vs. 28.6%; p = .68). In propensity analysis, the IPTW‐adjusted models showed no significant association between the use of DPP‐4 inhibitors and the primary outcome by Day 7 (OR [95% CI]: 0.95 [0.77–1.17]) or Day 28 (OR [95% CI]: 0.96 [0.78–1.17]). Similar neutral findings were found between use of DPP‐4 inhibitors and the risk of tracheal intubation and death. Conclusions: These data support the safety of DPP‐4 inhibitors for diabetes management during the COVID‐19 pandemic and they should not be discontinued.